Study on spatial variation of water quality in Sungai Tunggak, Kuantan, Pahang - Nur Fairuz, Mohd Maliki (2014)
A study on spatial variation of water quality in Sungai Tunggak, Gebeng Pahang was conducted at five sampling stations which were at Padang Tebing Tinggi, Perkampungan Seberang Balok 1, Taman Balok Makmur & Perkampungan Seberang Balok, entrance of Gebeng Industrial Area and Gebeng Industrial Area. A total of twelve water quality parameters were analysed including in situ test and laboratory analysis (ex-situ test). All the parameters were analysed and measured according to standard method. The physical, chemical and biological variables were temperature, pH value, turbidity, total suspended solids (TSS), dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), electrical conductivity (EC), ammonical nitrogen (Nm-N), total coliform and Escherichia coli (E.Coli). The result show that water quality at Sungai Tunggak is Class ffi based on Water Quality Index (WQI), which means, Sungai Tunggak is suitable for water supply. However, extensive treatment required for water supply. Human activities at surrounding area near Sungai Tunggak affected water quality there. Agricultural and farming activity also commercial activity at Taman Balok Makmur & Perkampungan Seberang Balok and residential area at Perkampungan Seberang Balok 1 indeed affects water quality in Sungai Tunggak and if these situation continued, may have caused environmental degradation at Sungai Tunggak hence may lead alga bloom in river. Regarding heavy metals values of lead (Pb), cadmium (Cd), ferum (Fe) and manganese (Mn) was recorded in toxic level in the surface water of the river except zinc (Zn).